Association Between Learning Approaches and Medical Student Academic Progression During Preclinical Training - Bansal S (Dove Medical Press, 2021)
Sandeep Bansal,1 Minakshi Bansal,2 Stanley White3 1Department of Medical Education, TCU and UNTHSC School of Medicine, Fort Worth, TX, USA; 2Harris College of Nursing and Health Sciences, Texas Christian University, Fort Worth, TX, USA; 3All Saints University School of Medicine, Roseau, Commonwealth of DominicaCorrespondence: Sandeep BansalDepartment of Medical Education, TCU & UNTHSC School of Medicine, Fort Worth, TX, USAEmail Sandeep.Bansal@tcu.eduPurpose: Students have diverse learning preferences that can impact the achievement of learning outcomes. However, there is a lack of unequivocal evidence for an association between the learning preferences and academic success. The purpose of the study was to examine the association between learning approaches and academic success of medical students during the basic science curriculum.Methods: In this cross-sectional comparative study, low-achieving (n=80) and high-achieving students (n=50) from semesters 1 through 3 of the Ross University School of Medicine’s basic science curriculum completed the Approaches and Study Skills Inventory for Students (ASSIST) short-form to provide data on their learning approaches. Student’s-t test was applied to find statistical differences in learning approaches of low and high achievers, and point-biserial was used to analyze the correlation between academic performance and learning approaches. Mean sum scores with standard deviation on ASSIST short-form scales (deep, surface, and strategic approaches) as well as subscales are reported.Results: High-achieving students reported a preference for using deep and strategic learning approaches compared to low-achieving students (p < 0.05). Low achievers indicated that they predominantly used the surface approach to learning (p< 0.05). Yet, “fear of failure,” a subscale of the surface approach, was greater among high achievers. Additionally, significant gender differences were found on subscales of “lack of purpose,” “syllabus bound,” “unrelated memorization” (surface approach), and “time management” and “organized studying” (strategic approach).Conclusion: Our results suggest that low-achieving medical students’ predominant reliance on the surface approach to learning may affect their academic success and that it may be worthwhile to help medical students become aware of the effectiveness of their individual preferred learning approaches early on in their training. Identification and adoption of optimal learning approaches should increase the achievement of successful learning outcomes.Keywords: learning approaches, learning outcomes, remediation, medical curriculum, ASSIST short-form